2010
DOI: 10.1074/jbc.m109.098558
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Mixed Lineage Leukemia 5 by Cdc2 Affects Its Cellular Distribution and Is Required for Mitotic Entry

Abstract: The human mixed lineage leukemia-5 (MLL5) gene is frequently deleted in myeloid malignancies. Emerging evidence suggests that MLL5 has important functions in adult hematopoiesis and the chromatin regulatory network, and it participates in regulating the cell cycle machinery. Here, we demonstrate that MLL5 is tightly regulated through phosphorylation on its central domain at the G 2 /M phase of the cell cycle. Upon entry into mitosis, the phosphorylated MLL5 delocalizes from condensed chromosomes, whereas after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
3
19
0
1
Order By: Relevance
“…To study if the affinity of p53 to DNA was affected by downregulation of MLL5, cellular fractionation was performed in scrambled or MLL5-siRNAtransfected HCT116 cells. Consistent with the previous reports (Deng et al, 2004;Liu et al, 2010b), MLL5 was primarily detected in the chromatin-associated fraction (Figure 4e). Interestingly, a detectable translocation of p53 from the nucleoplasmic to the chromatin-associated fraction was observed upon MLL5 knockdown, an indication of an enhanced recruitment of p53 to its target site (Figure 4e).…”
Section: Mll5 Negatively Regulates P53 At a Post-translational Levelsupporting
confidence: 93%
See 3 more Smart Citations
“…To study if the affinity of p53 to DNA was affected by downregulation of MLL5, cellular fractionation was performed in scrambled or MLL5-siRNAtransfected HCT116 cells. Consistent with the previous reports (Deng et al, 2004;Liu et al, 2010b), MLL5 was primarily detected in the chromatin-associated fraction (Figure 4e). Interestingly, a detectable translocation of p53 from the nucleoplasmic to the chromatin-associated fraction was observed upon MLL5 knockdown, an indication of an enhanced recruitment of p53 to its target site (Figure 4e).…”
Section: Mll5 Negatively Regulates P53 At a Post-translational Levelsupporting
confidence: 93%
“…Upon MLL5 knockdown, the entry of quiescent myoblasts into S-phase was delayed, but the completion of S-phase progression was hastened (Sebastian et al, 2009). Recently, we showed that phosphorylation of MLL5 by mitotic kinase Cdc2 is required for mitotic entry (Liu et al, 2010b). Taken together, these data imply that MLL5 have different regulatory roles throughout cell cycle.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, phosphorylation signaling has been shown to play an essential role in regulating the function and interaction between proteins, maintaining the stability and participating in the localization of the protein. Recently, it was suggested that the phosphorylation modification on Thr-912 residue of MLL protein controls its subcellular localization and is required for mitotic entry (41). In the present study, we showed that iloprost suppressed poly I:C-induced phosphorylation of MAPK-p38, and by using the MAPK-p38 inhibitor SB203580, we also showed that the poly I:C-induced translocation of MLL and WDR5 proteins from cytoplasm to nucleus was MAPKp38 dependent.…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 68%